2016
DOI: 10.1038/npp.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Specific Involvement of (+)-Naloxone and (+)-Naltrexone on the Reinforcing and Neurochemical Effects of Cocaine and Opioids

Abstract: Effective medications for drug abuse remain a largely unmet goal in biomedical science. Recently, the (+)-enantiomers of naloxone and naltrexone, TLR4 antagonists, have been reported to attenuate preclinical indicators of both opioid and stimulant abuse. To further examine the potential of these compounds as drug-abuse treatments, we extended the previous assessments to include a wider range of doses and procedures. We report the assessment of (+)-naloxone and (+)-naltrexone on the acute dopaminergic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 47 publications
1
56
0
Order By: Relevance
“…Tanda and his colleagues further assessed specificity of the blocking effects of the TLR4 antagonists on self-administration of remifentanil or cocaine [5]. Consistent with the results from the two earlier studies [3,4], both (+)-naloxone and (+)-naltrexone dose-dependently produced an insurmountable antagonism against self-administration of remifentanil or cocaine.…”
Section: Editorialsupporting
confidence: 67%
See 4 more Smart Citations
“…Tanda and his colleagues further assessed specificity of the blocking effects of the TLR4 antagonists on self-administration of remifentanil or cocaine [5]. Consistent with the results from the two earlier studies [3,4], both (+)-naloxone and (+)-naltrexone dose-dependently produced an insurmountable antagonism against self-administration of remifentanil or cocaine.…”
Section: Editorialsupporting
confidence: 67%
“…These findings suggested a "novel" TLR4-mediated mechanism underlying the reinforcing effects of drugs of abuse across pharmacological classes. A more recent study [5] has, however, indicated that the TLR4 hypothesis is less viable.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations